Aplikasi Penggunaan Metode Moire Pattern untuk Mengetahui Karakteristik Sebaran Nilai Stress-Displacement pada Material Baja AISI 304 Berbasis Image Processing - Mohammad Khoirul Effendi; Agus Sigit Pramono; Ari Surya Yulianto; Hanif Pribadi (Jurnal Teknik Mesin (Sinta 3), 2014)
Stress field is an important parameter for determining the strength of a plate due the loading. Measurement of the stress field in it cannot be done directly. The mathematic explanation shows that the stress field has a relationship with the terrain displacement/displacement. In the plate theory, deflection is defined as displacement towards out plane direction. One method to get the value of deflection on the plate is a moiré method. This moiré method uses the principle of line superposition between plate and its reference. When a test plate subjected to a load, the deflection that occurs in the test material a pattern will be produced in the form of a superposition of light and dark pattern (fringe) which describes the distribution of the stress-displacement on a surface of tested material. Tested material is AISI 304.The surface of tested material was given a lattice pattern with variations in distance of 1 mm. The fourth side of the tested plate is clamped perfectly, then the center of it will be pressurized with variations in displacement (0.5, 1, 1.5, and 2 mm). The occurred Moiré patterns will be captured by the camera to turn it into a digital image. Furthermore, it will be processed through a series of image processing which consists of the four different filter algorithms (Gaussian filter and Butterworth Low Pass Filter), and also four edge detection algorithms (Sobel, Prewitt, Canny, and Roberts).The results of the stress-strain measurements will be compared with the results of analytical calculations and numerical calculations. The difference of displacement average using ​​moiré method compared with analytical method is 6.75%, while using numerical method is 7.55%. Furthermore the difference of stress average using ​​moiré method compared with analytical calculation is 9:08%, while using numerical methods by 9.5%.